Pulsatile ocular blood flow in asymmetric exudative age related macular degeneration. Issue 12 (1st December 2001) - Chen, Shih-Jen; Cheng, Ching-Yu; Lee, An-Fei; Lee, Fenq-Lih; Chou, Joe C.K.; Hsu, Wen-Ming; Liu, Jorn-Hon
Abstract : BACKGROUND/AIMS: Decreased perfusion or increased vascular resistance of the choroidal vessels had been proposed as the vascular pathogenesis for age related macular degeneration (AMD). This study planned to answer the question whether pulsatile ocular blood flow (POBF) was different in patients with asymmetric exudative AMD between eyes with drusen, choroidal neovascularisation (CNV), or disciform scar. METHODS: 37 patients with asymmetric exudative AMD were enrolled in this observational case series study. POBF were measured in both eyes of each subject. Eyes with high myopia, anisometropia, recent laser treatment, and glaucoma were excluded. RESULTS: After adjusting for ocular perfusion pressure, intraocular pressure, and pulse rate, multivariate regression analysis with generalised estimating equation showed POBF was significantly higher in eyes with CNV (1217 (SD 476) μl/min) than the contralateral eyes with drusen (1028 (385) μl/min) (p = 0.024). Eyes with disciform scar had lower POBF than the contralateral eyes with drusen (999 (262) μl/min and 1278 (341) μl/min, respectively, p<0.001). There was no significant correlation between the POBF and the lesion size of the CNV. CONCLUSION: The POBF in eyes with drusen was lower than their fellow eyes with CNV, but higher than their fellow eyes with disciform scar. This finding suggests that haemodynamic differences between fellow eyes in individuals are relevant to the development of CNV and the formation of disciform scar. Further studies on the follow up patients might shed light on the pathogenesis of exudative AMD.